Bibliometric Analysis of Studies on Neuropathic Pain Associated With Depression or Anxiety Published From 2000 to 2020 - Li, Kai-Li-Mi; Chen, Yu-Meng; Wang, Xue-Qiang; Hu, Hao-Yu (Frontiers in Human Neuroscience, 2021)
Objective: Neuropathic pain (NP) associated with depression or anxiety is highly prevalent in clinical practice. Publications about NP associated with depression or anxiety increased exponentially from 2000 to 2020. However, studies that applied the bibliometric method in analyzing global scientific research about NP associated with depression or anxiety are rare. This work used the bibliometric method to analyze the publications on NP associated with depression or anxiety between 2000 and 2020. Method: Publications from 2000 and 2020 were identified from the Thomson Reuters Web of Science (WoS) database. We employed CiteSpace V to conduct the bibliometric study. Results: A total of 915 articles or reviews were obtained from the WoS database. The number of publications has increased over the last two decades. The USA was the most productive among countries or regions in the field. According to the burst key words, neuroinflammation, hippocampus, safety, and modulation were the hot global research issues in the domain. Conclusion: Publications about NP associated with depression or anxiety have remarkably increased from 2000 to 2020. These historical opinions about NP associated with depression or anxiety could be an important practical basis for further research into potential development trends.